Bargaining and Distribution of Power in the EU's Conciliation Committee - Stefan Napel; Mika Widgrén (Center for Economic Studies and ifo Institute (CESifo), 2003)
The European Union (EU) has moved towards bicameralism, making the codecision procedure its most important mechanism for decision making. To gauge if European Parliament (EP) and Council of Ministers (CM) are equally powerful codecision makers', understanding of the final stage of the procedure - bargaining in the Conciliation Committee - is crucial. Here, EP and CM are assumed to have spatial preferences determined by their respective internal decision mechanisms. Applying bargaining theory to predict inter-institutional agreements in the Conciliation Committee, it turns out that although institutionally the Council and the Parliament are seemingly in a symmetric position, CM has significantly greater influence on EU legislation.
Keywords: 330; European Union codecision procedure; Conciliation Committee; bargaining; spatial voting; decision procedures